Differential Toxicity of Disperse Red 1 and Disperse Red 13 in the Ames Test, HepG2 Cytotoxicity Assay, and Daphnia Acute Toxicity Test - Ferraz, E. R. A.; Umbuzeiro, G. A.; de-Almeida, G.; Caloto-Oliveira, A.; Chequer, F. M. D.; Zanoni, Maria Valnice Boldrin [UNESP]; Dorta, D. J.; Oliveira, D. P. (Wiley-Blackwell, 2011)
Azo dyes are of environmental concern due to their degradation products, widespread use, and low-removal rate during conventional treatment. Their toxic properties are related to the nature and position of the substituents with respect to the aromatic rings and amino nitrogen atom. The dyes Disperse Red 1 and Disperse Red 13 were tested for Salmonella mutagenicity, cell viability by annexin V, and propidium iodide in HepG2 and by aquatic toxicity assays using daphnids. Both dyes tested positive in the Salmonella assay, and the suggestion was made that these compounds induce mainly frame-shift mutations and that the enzymes nitroreductase and O-acetyltransferase play an important role in the observed effect. In addition, it was shown that the presence of the chlorine substituent in Disperse Red 13 decreased the mutagenicity about 14 times when compared with Disperse Red 1, which shows the same structure as Disperse Red 13, but without the chlorine substituent. The presence of this substituent did not cause cytotoxicity in HepG2 cells, but toxicity to the water flea Daphnia similis increased in the presence of the chlorine substituent. These data suggest that the insertion of a chlorine substituent could be an alternative in the design of dyes with low-mutagenic potency, although the ecotoxicity should be carefully evaluated. (C) 2010 Wiley Periodicals, Inc. Environ Toxicol 26: 489-497, 2011.
Keywords: azo dyes; Disperse Red 1; Disperse Red 13; chlorine substituent; Salmonella mutagenicity assay; Daphnia similis